Evaluation of Molina-Albir Translation Techniques Comprehension in Translation Class - Hidayat, Arif; Lustyantie, Ninuk; Murtadho, Fathiaty (JET (Journal of English Teaching), 2024)
Translation is crucial in cross-cultural communication, especially in today's globalized world. Understanding translation techniques, such as the Molina-Albir technique, is key to producing high-quality translations. This study aims to evaluate the understanding and application of Molina-Albir translation techniques among English Literature students at Bina Sarana Informatics University. This descriptive qualitative research involves observing and analyzing the translation work of peers. It focuses on students in class 33.6A during the Even Period of 2022-2023, who will analyze their classmates' translations based on detailed instructions. Data is analyzed both qualitatively and quantitatively, with results validated by researchers and/or lecturers. The study found that 68% of students had a fair to very good understanding of Molina-Albir techniques, while many scored below 60%. Key issues included misidentification of techniques such as amplification, modulation, and adaptation, indicating a need for improved teaching methods.